Fomentando bons negócios: uma pesquisa-ação com foco no aperfeiçoamento de práticas colaborativas entre scale-ups e corporações, apoiadas por uma organização intermediária - Assis, Mariela C. S. Fontenelle Sily de (2023)
The collaboration between corporations and scale-ups – high-growth companies with a scalable and innovative business model – can generate significant impacts for their entrepreneurs. The relationship between these inherently different partners is asymmetrical. Much of the research adopts the perspective of large companies or institutions. The lack of understanding of the scale-ups’ perspective brings risks to the sustainability of the collaboration and the maximization of the value generated by the partnership. This study aimed to help improve the practices of a global non-profit organization that acts as an intermediary supporting corporations and scale-ups in open innovation initiatives, as well as to broaden the understanding of how scale-ups perceive the generation of good business with corporations. The study, which lasted 21 months, used action research as the research approach and interorganizational collaboration as the theoretical lens. The results of the study reveal the entrepreneurs’ views on what constitutes good business with corporations, the ways in which this engagement contributes to the growth challenges of scale-ups, and the practices that enhance good business between the parties. The study provides contributions to both practice and theory. For practice, based on lessons learned from the experiences of scale-up entrepreneurs, the study proposes a framework for good business, containing collaborative practices between corporations and scale-ups, as well as specific recommendations for each party and intermediary organizations. It is expected that these contributions will benefit organizations and practitioners involved in such connections, aiming to maximize the value generated by the collaboration between these partners. In terms of theory, the study contributes to the literature on “collaboration between corporations and startups” by providing insights from entrepreneurs leading scale-ups regarding collaboration with corporations in open innovation initiatives.